2000
DOI: 10.5507/bp.2000.002
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Family: From Genes to Human Disease

Abstract: Interleukin-1 (IL-1) is one of the most potent proinflammatory cytokines involved both in physiological immune responses and in the development of various immunopathological disorders. The members of IL-1 family form a complex system with tight regulatory mechanisms and clarifying their role in disease remains in the centre of research interests. This review article except of summarising recent findings about IL-1 family members focuses on associations of IL-1 gene complex polymorphisms with human diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 140 publications
0
18
0
1
Order By: Relevance
“…25 These three polymorphisms directly affect protein structure and alter its function, not by affecting the sequence of amino acids in polypeptide chains, but rather at different transcriptional or post-transcriptional levels by altering the structure of the gene's regulatory elements with binding sites for transcription factors, transcription rate, mRNA splicing, and mRNA stability. 26 Genetically, we need to understand which alleles are linked. It follows that the linkage disequilibrium (LD) and haplotype structure of a candidate gene is important for association analyses to understand how polymorphisms contribute to the risk of disease and population variance of certain phenotypes of interest.…”
Section: Introductionmentioning
confidence: 99%
“…25 These three polymorphisms directly affect protein structure and alter its function, not by affecting the sequence of amino acids in polypeptide chains, but rather at different transcriptional or post-transcriptional levels by altering the structure of the gene's regulatory elements with binding sites for transcription factors, transcription rate, mRNA splicing, and mRNA stability. 26 Genetically, we need to understand which alleles are linked. It follows that the linkage disequilibrium (LD) and haplotype structure of a candidate gene is important for association analyses to understand how polymorphisms contribute to the risk of disease and population variance of certain phenotypes of interest.…”
Section: Introductionmentioning
confidence: 99%
“…This gene cluster includes, within a 360-kb region, the IL-1␣ (IL1A), IL-1␤ (IL1B), IL1F7, IL1F9, IL1F6, IL1F8, IL1F5, IL1F10, and IL-1 receptor antagonist (IL1RN) genes. The IL1F5-IL1F10 genes in this cluster are widely expressed, including on activated monocytes and B cells, and signal through a range of IL-1 receptors (9,10). Several may function as IL-1 antagonists due to their sequence similarity to IL1RN, although their function is largely unknown.…”
mentioning
confidence: 99%
“…Although these four SNPs do not occur in a coding region, these germ line variants may still influence protein production by transcriptional or posttranscriptional activities (22) including transcriptional factors, transcription rate, messenger RNA splicing or messenger RNA stability (23). In silico analyses using SNPInfo (24) revealed that the rs1047275 locus is located in the binding sites for miR-379 and miR-473 and may potentially regulate TNFRSF10B expression.…”
Section: Discussionmentioning
confidence: 99%